TUBE CYSTOSTOMY FOR SURGICAL MANAGEMENT OF OBSTRUCTIVE UROLITHIASIS IN SHEEP AND GOATS - Pandiyan; Mala Shammi; Ravi Sundar George; S.Vairamuthu (Indian Journal of Veterinary and Animal Sciences Research, 2023)
Obstructive urolithiasis is a serious and potentially fatal condition in male small ruminants. It is caused by obstruction of urethral lumen at the distal portion of the sigmoid flexure and at the urolithic process. The aim of this study was to evaluate the efficacy of surgical tube cystostomy in the management of obstructive urinary calculi in male sheep and goat. A total of 6 animals were studied (sheep-2 and goat-4) that were referred to Large animal clinics - Out Patient- Surgery Unit of Madras Veterinary College Teaching Hospital with a history of anuria, dysuria and stranguria. In Tube cystostomy, the animals were positioned in right lateral recumbency. The bladder was approached in left paramedianregion cranial to the last pair of rudimentaryteats. The urine was drained and calculi in the bladder was removed with the forceps. The catheter was fixed in the urinary bladder by meansof purse string suture pattern using 3/0 or4/0 polyglecaprone. Then the abdominal muscles and skin were apposed. Biochemical analysis revealed significant increase in BUN & Creatinine pre-operatively and decreases post operatively. Postoperatively normograde contrast cystourethrography on day 1 revealed filling defect of contrast agent showing obstruction at the level of Sigmoid Flexure. Ultrasonographic examination after normal urination revealed presence of calculi and also the site of obstruction in the bladder. The time period taken to return for normal urination in Tube Cystostomy was (10.66 ± 0.06 days) and the wound healing of the surgical site was better in tube cystomy.